Asphyxiating impediments in access to equal right to education for persons with disabilities in Africa (2018)
Disability does not disqualify a person from the enjoyment of the right to education and other social benefits, out in practice certain impediments limit the access of persons with disabilities (PWDs) to the right to education -weed Tie right to education is a key that unlocks other rights and therefore has a multiplier effect in terms of its benefits This article examined how the right to education though provided for in various international, regional and national instruments in recognition of its importance, still eludes many PWDs in Africa due to certain impediments The methodology for the research is doctrinal and analytical. The result shows that although the various provisions — legal instruments to guarantee equality of the right to education ought to make much more difference to the level of access to education for PWDs, it has not been so especially in Africa, due to several impediments. The impediments social and physical, include discrimination on grounds of disability, lack of funding, lack of materials in accessible formats such as Braille, sign language or visual representations of verbal information, lack of teacher training programs, occasioning in a scarcity of qualified teachers and support staff. Other impediments include lack of accessible and affordable means of transportation. To ensure that the right to education achieves its goals in the lives of PWDs and the society reaps the benefits thereof, the paper concludes by recommending affirmative action, better funding, deliberate training of qualified teachers and other measures to make equal right to education a reality and not just a paper Tiger for PWDs in Africa.